Preparation of Nanostructured Mixed Lithium Zirconium Oxides by Spray Pyrolysis

The particle properties of lithium-zirconium mixed oxides are optimized through flame spray pyrolysis and heat treatment, and the problem of insufficient particle size and surface area in the prior art is solved, and the circulation performance and stability of lithium-ion batteries are improved.

CN114401928BActive Publication Date: 2024-12-31EVONIK OPERATIONS GMBH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202080063815.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-09-10
Publication Date
2024-12-31
Estimated Expiration
2040-09-10

AI Technical Summary

Technical Problem

The prior art is difficult to prepare lithium-zirconium mixed oxides with small particle size, high BET surface area and low compaction density by spray pyrolysis, resulting in poor circulation performance of lithium-ion batteries.

Method used

Using flame spray pyrolysis method, lithium carboxylate and zirconium carboxylate are used as metal precursors, combining solvent mixtures of alcohol and carboxylic acids, and highly dispersed metal oxide particles are generated by flame oxidation and hydrolysis, and further heat treatment and ball milling are carried out to optimize Granular properties.

Benefits of technology

Li-zirconium mixed oxides with small particle size, high BET surface area and low compaction density were obtained, which improved the performance of the active electrode material of lithium-ion batteries and enhanced the cycle stability and energy density of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003542241980000011
    Figure HDA0003542241980000011
  • Figure HDA0003542241980000012
    Figure HDA0003542241980000012
  • Figure HDA0003542241980000021
    Figure HDA0003542241980000021
Patent Text Reader

Abstract

The present invention relates to a process for producing a mixed oxide comprising lithium and zirconium and optionally at least one non-lithium, non-zirconium metal by flame spray pyrolysis, the mixed oxide obtainable by the process and the use thereof in lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a process for producing a mixed oxide comprising lithium and zirconium and optionally at least one non-lithium, non-zirconium metal by flame spray pyrolysis, the mixed oxide obtainable by the process and the use thereof as active cathode material in lithium-ion batteries. Prior art

[0002] Secondary lithium-ion batteries are one of the most important types of batteries in use today. Secondary lithium-ion batteries are usually composed of an anode made of carbon material or lithium metal alloy, a cathode made of lithium-metal oxide, a liquid electrolyte in which lithium salts are dissolved in an organic solvent, and a separator that provides a passage for lithium ions between the positive and negative electrodes during the charging and discharging process.

[0003] In an effort to develop secondary batteries with improved inherent safety and energy density, great progress has recently been made using solid electrolytes instead of liquid electrolytes. Among these systems, secondary lithium batteries with electrodes made of lithium metal or lithium metal alloys are considered to provide high energy density and are particularly suitable. This all-solid-state secondary lithium-ion battery should have good ionic conductivity at the interface between the electrode active material and the electrolyte to have the desired load characteristics. As described in JP4982866B2, this high ionic conductivity can be achieved by coating the surface of the active electrode material with some lithium-containing compounds such as LiTi2(PO4)3.

[0004] Lithium-containing mixed oxides have various applications in both solid-state and liquid lithium-ion batteries.

[0005] Thus, in Agnew.Chem.Int.,Ed.2007,46,1-55, it is reported that Li7La3Zr2O 12 (LLZ) and garnet-type structured mixed oxides have excellent lithium resistance and can be used as solid electrolytes in all-solid-state lithium secondary batteries.

[0006] EP 2159867 A1 describes the preparation of an improved aluminum-doped LLZ material for use in solid electrolytes. Thus, lithium carbonate, lanthanum hydroxide and zirconium oxide are mixed together and calcined at 900-1125° C. Al2O3 is then added to the calcined LLZ material, followed by a second calcination at 1180° C. to obtain a density of about 4 g / cm 3 Al-doped LLZ oxide.

[0007] Similar mixed oxides are also reported to be used as coating materials for secondary lithium battery electrodes.

[0008] One of the common problems with cathode materials for lithium batteries is that they age quickly and therefore lose performance during cycling. It is well known that coating or doping mixed lithium transition metal oxide particles with certain metal oxides can inhibit unwanted reactions of the electrolyte with the electrode material and thus improve the long-term stability of lithium-ion batteries.

[0009] Among other metal oxides, zirconium-containing mixed oxides have been reported for this purpose.

[0010] US2017179544A discloses the preparation of zirconium-based lithium positive electrode materials doped with mixed metal oxides. Therefore, in Example 1, Li7La3Zr2Al 0.07 O 12.0105 The method is to mix the metal salts and sinter the mixture at 1200°C for 10 hours, and then mix with the mixed lithium transition metal oxide Li (Li 10 / 75 Ni 18 / 75 Co 9 / 75 Mn 38 / 75 )O2 dry mixed and then heated at 900 ° C for 20 hours to form a lithium positive electrode material. It is obvious from the preparation procedure that only Li7La3Zr2Al can be used in this example. 0.07 O 12.0105 Large size sintered particles.

[0011] The use of such relatively large zirconium-containing metal oxide particles generally results in unevenly distributed and large agglomerated metal oxide particles on the surface of the core cathode material, and thus, little or no improvement in cycling performance is observed when compared to undoped or uncoated cathode materials.

[0012] Spray pyrolysis is a known process for producing relatively small metal oxide particles.

[0013] Spray pyrolysis and flame spray pyrolysis are established processes for the production of simple metal oxides as well as complex mixed metal oxides. In spray pyrolysis, metal compounds in the form of fine droplets are introduced into a high temperature zone where they are oxidized and / or hydrolyzed to give metal oxides. A special form of the process is flame spray pyrolysis, in which the droplets are supplied to a flame formed by igniting a fuel gas and an oxygen-containing gas.

[0014] WO 2015173114 A1 describes a flame spray pyrolysis method for producing a mixed oxide powder containing lithium, lanthanum, zirconium and optionally other metals, which uses a corresponding solution of a precursor compound containing lithium, lanthanum, zirconium and optionally other metal compounds MX as a starting material. As metal precursor compounds, it is recommended to use inorganic compounds such as nitrates, chlorides, bromides or organic compounds such as alkoxides or carboxylates. Preferred embodiments of the patent application include nitrates of lithium, lanthanum, zirconium and other metals. As solvents for metal precursors, it is recommended to use water, C5-C 20 Alkanes, C1-C 15 Alkane carboxylic acids and / or C1-C 15 Alkanols, preferably water and solvent mixtures containing water. In all examples, water was used as the only solvent for the metal nitrate precursors. The BET surface area of ​​the resulting mixed oxides was in the range of 0.19-5.1 m 2 / g range, the average particle size (d 50 ) is about 2-3μm.

[0015] J. Mater. Chem. A, 2016, Vol. 4, pp. 12947-12954 discloses a method for preparing a Li 2-carbon ... 6.25 Al 0.25 La3Zr2O 12 , BET surface area is 16m 2 / g, a powder with a primary particle size of 90 nm and an agglomerate particle size of about 5 μm.

[0016] Problems and Solutions

[0017] The cited prior art documents teach the production of mixed lithium zirconium metal oxides by spray pyrolysis. However, the resulting products are reported to have larger particle sizes, lower BET surface areas, and generally higher densities.

[0018] The problem addressed by the present invention is to provide an improved process for producing mixed lithium zirconium metal oxides which can be used in secondary lithium-ion batteries, for example as a component of a solid electrolyte or as a constituent of an electrode material.

[0019] In particular, the process should provide metal oxide particles having a relatively small particle size, a high BET surface area and a low packed density.

[0020] During intensive experiments, it was surprisingly found that, when using a specific combination of metal precursors and solvents, lithium zirconium mixed oxides having the desired particle properties can be prepared by flame spray pyrolysis.

[0021] Process for producing mixed oxides

[0022] The present invention provides a process for producing a mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal by flame spray pyrolysis and optionally further heat treatment, characterized in that the process uses

[0023] A solution of at least one metal precursor comprising

[0024] - lithium carboxylates and / or zirconium carboxylates, wherein each of these metal carboxylates contains from 5 to 20 carbon atoms, and

[0025] - a solvent mixture comprising an alcohol containing 5 to 20 carbon atoms and a carboxylic acid, wherein the solvent mixture comprises less than 10% by weight of water and wherein the molar ratio of alcohol to carboxylic acid is between 1:20 and 20:1.

[0026] During the flame spray pyrolysis process, a solution of metal compounds (metal precursors) is introduced in the form of fine droplets into a flame formed by igniting a fuel gas and an oxygen-containing gas, wherein the metal precursors used are oxidized and / or hydrolyzed to give the corresponding metal oxides.

[0027] The reaction initially forms highly dispersed approximately spherical primary metal oxide particles, which coalesce to form aggregates during further reaction. The aggregates can then accumulate into agglomerates. Contrary to agglomerates that can usually be separated into aggregates relatively easily by introducing energy, if at all, the aggregates can only be further decomposed by strongly introducing energy.

[0028] The metal oxides produced are referred to as "fume phase" or "pyrolytically produced" metal oxides.

[0029] Flame spray pyrolysis processes are generally described in WO 2015173114 A1 and elsewhere.

[0030] The flame spray pyrolysis preferably comprises the following steps:

[0031] a) atomizing at least one metal precursor solution by means of an atomizer gas to provide an aerosol,

[0032] b) reacting the aerosol in the reaction space of the reactor with a flame obtained by igniting a mixture of fuel gas and oxygen-containing gas to obtain a reaction stream,

[0033] c) cooling the reaction stream and

[0034] d) subsequently removing the solid metal oxide from the reaction stream.

[0035] Examples of fuel gases are hydrogen, methane, ethane, natural gas and / or carbon monoxide. Hydrogen is particularly preferably used. Fuel gases are particularly useful in embodiments where it is desired that the produced metal oxide has a high degree of crystallinity.

[0036] The oxygen-containing gas is generally air or oxygen-enriched air. Oxygen-containing gases are particularly useful in embodiments where, for example, it is desired that the metal oxide produced has a high BET surface area. The total amount of oxygen is generally selected so that it is at least sufficient to completely convert the fuel gas and the metal precursor.

[0037] In order to obtain an aerosol, the vaporized solution containing the metal precursor can be mixed with an atomizer gas such as nitrogen, air and / or other gases. The fine droplets of the obtained aerosol preferably have an average droplet size of 1-120 μm, particularly preferably 30-100 μm. The droplets are usually produced using a single-material or multi-material nozzle. In order to increase the solubility of the metal precursor and obtain a suitable viscosity for atomization of the solution, the solution can be heated.

[0038] The metal precursor used in the method of the present invention comprises at least one lithium carboxylate and at least one zirconium carboxylate, each containing from 5 to 20 carbon atoms.

[0039] The lithium and zirconium carboxylates used in the process according to the invention may independently be linear, branched or cyclic lithium and / or zirconium valerates (C5), hexanoates (C6), heptanoates (C7), octanoates (C8), nonanoates (C9), decanoates (D10), undecanoates (C11), dodecanoates (C12), tridecanoates (C13), tetradecanoates (C14), pentadecanoates (C15), hexadecanoates (C16), heptadecanates (C17), octadecanoates (C18), nonadecanates (C19), eicosanoates (C20) and mixtures thereof.

[0040] Most preferably, zirconium 2-ethylhexanoate (C8) and lithium neodecanoate (C10) are used.

[0041] The metal precursor used may comprise a carboxylate of a non-lithium, non-zirconium metal.

[0042] Besides precursors of lithium and zirconium, the metal precursor may also be an inorganic metal compound such as nitrate, chloride, bromide, or other organometallic compounds such as alkoxides, for example ethoxide, n-propoxide, isopropoxide, n-butoxide and / or tert-butoxide.

[0043] The at least one non-Li non-Zr metal optionally contained in the mixed oxide may preferably be selected from Na, K; Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, B, Al, Ga, In, Fe, Sc, Y, La, Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, V, Nb, Ta, Mo, W and combinations thereof. In the context of the present invention, silicon dioxide and boron are regarded as metals, and their compounds can also be used as metal precursors in the process of the present invention. Preferably, the mixed oxide of the present invention comprises lanthanum (La) and aluminum (Al).

[0044] The solvent mixture used in the process of the present invention for dissolving the metal precursor comprises an alcohol containing 5 to 20 carbon atoms and a carboxylic acid.

[0045] The alcohol is preferably selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, n-pentanol, n-hexanol, cyclohexanol, n-octanol, 2-ethylhexanol, n-decanol, neodecanol and mixtures thereof.

[0046] The carboxylic acid is preferably selected from linear, branched or cyclic pentanoic acid (C5), hexanoic acid (C6), heptanoic acid (C7), octanoic acid (C8), nonanoic acid (C9), decanoic acid (D10), undecanoic acid (C11), dodecanoic acid (C12), tridecanoic acid (C13), tetradecanoic acid (C14), pentadecanoic acid (C15), hexadecanoic acid (C16), heptadecanoic acid (C17), octadecanoic acid (C18), nonadecanoic acid (C19), eicosanoic acid (C20) and mixtures thereof.

[0047] The molar ratio of alcohol to carboxylic acid in the solvent mixture used in the present invention is between 1:20 and 20:1, preferably between 1:15 and 15:1, more preferably between 1:10 and 10:1, most preferably between 1:6 and 6:1.

[0048] The solvent mixture used in the present invention comprises less than 10 wt % water, preferably less than 5 wt % water, more preferably less than 3 wt % water, even more preferably less than 2 wt % water, still more preferably less than 1 wt % water.

[0049] The total metal content in the solution of the metal precursor is preferably 1 wt%-30 wt%, more preferably 2 wt%-20 wt%, even more preferably 3 wt%-15 wt%. "Total metal content" is understood as the total weight proportion of all metals contained in the metal precursor in the solution of the metal precursor used.

[0050] The solvent mixture used for the inventive method may additionally contain a chelating agent, i.e. a compound capable of forming two or more coordination bonds with the metal ion. Examples of such chelating agents are, for example, diamines such as ethylenediamine, ethylenediaminetetraacetic acid (EDTA), 1,3-dicarbonyl compounds such as acetylacetone and alkyl acetoacetates. Most preferably, acetylacetone is used as such a chelating agent.

[0051] It was observed that in the presence of such chelating agents, some metal precursors (eg, zirconium compounds) exhibited better solubility and no precipitation after relatively long storage times.

[0052] The use of a specific combination of metal precursors and solvent mixture according to the invention allows ensuring good solubility of all metal precursors and achieving the desired metal oxide particle properties, such as small particle size, high BET surface area and low tamped density.

[0053] The process according to the invention may comprise the step of subjecting the mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal produced by flame spray pyrolysis to a further heat treatment.

[0054] The further heat treatment is preferably carried out at a temperature of 600-1300°C, more preferably 650-1250°C, even more preferably 700-1200°C, still more preferably 750-1150°C.

[0055] The heat treatment according to the method of the invention allows obtaining a heat-treated metal oxide having the desired properties, in particular the desired crystal structure. Thus, for example, Li7La3Zr2O is treated at a temperature of about 800°C to 1200°C. 12 Performing a heat treatment allows the formation of mixed metal oxides with a cubic garnet crystal structure that are particularly suitable for use in solid electrolytes for lithium-ion batteries.

[0056] The process according to the invention may comprise the further step of grinding, preferably ball milling, the mixed oxide produced by flame spray pyrolysis comprising lithium, zirconium and optionally at least one non-Li, non-Zr metal.

[0057] Ball milling is preferably performed with ZrO2 balls, for example ZrO2 balls having a diameter of about 0.5 mm, in a suitable solvent such as ethanol or isopropanol.

[0058] Most preferably, the process of the present invention comprises both heat treatment and ball milling of the heat treated metal oxide.

[0059] The ball milling process according to the method of the invention allows obtaining ball milled metal oxides having the desired properties, in particular the desired crystal structure and particle size, which are particularly suitable for lithium ion batteries. Thus, ball milled and heat treated Li7La3Zr2O having a cubic garnet crystal structure and a desired particle size 12 Particularly suitable for solid electrolytes in lithium-ion batteries.

[0060] Mixed oxides

[0061] The mixed oxide prepared by the process according to the invention preferably has a 2 / g-100m 2 / g of BET surface area.

[0062] The unheat-treated mixed oxide, ie the product of the process according to the invention which has not been further heat-treated, preferably has a 2 / g-100m 2 / g, more preferably 7m 2 / g-70m 2 / g, most preferably 15-50m 2 / g of BET surface area.

[0063] The heat-treated mixed oxide, ie the product of the process according to the invention which has been further heat-treated, preferably has a carbon content of less than 10 m 2 / g, more preferably 0.1m 2 / g-10m 2 / g, more preferably 0.2m 2 / g-5m 2 / g, most preferably 0.3-3m 2 / g of BET surface area.

[0064] The heat-treated and ball-milled mixed oxide, ie the product of the process according to the invention after further heat treatment and ball milling, preferably has a 3m 2 / g-30m 2 / g, more preferably 4m 2 / g-25m 2 / g, most preferably 5m 2 / g-20m 2 / g of BET surface area.

[0065] The BET surface area can be determined in accordance with DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure.

[0066] As determined by transmission electron microscopy (TEM), the mixed oxide prepared by the method according to the invention is generally in the form of aggregated primary particles, the number average diameter of the primary particles being 5-100 nm, preferably 7-70 nm, more preferably 10-50 nm. The number average diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.

[0067] Number average particle size d of the (aggregated and agglomerated) mixed oxides 50 Typically it is about 0.05 μm to 3 μm, more preferably 0.1 μm to 2 μm, even more preferably 0.15 μm to 1.0 μm. The number average diameter can be determined by static light scattering (SLS) methods in a suitable dispersion, for example in an aqueous dispersion.

[0068] Agglomerates and a portion of aggregates may be disrupted, for example by grinding or sonicating the particles to produce particles having a smaller particle size and a narrower particle size distribution.

[0069] Preferably, the average particle size of the mixed oxide is d 200-100, as determined by static light scattering (SLS) after ultrasonication of a mixture consisting of 5% by weight of the particles and 95% by weight of a 0.5 g / L sodium pyrophosphate aqueous solution at 25° C. for 300 seconds. 50 It is 10-150 nm, more preferably 20-130 nm, even more preferably 30-120 nm.

[0070] The zirconium dioxide and / or zirconium-containing mixed oxide particles have a density (d ) of 0.147 W / L as determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25° C. for 300 seconds. 90 -d 10 ) / d 50 The range is preferably 0.4-1.2, more preferably 0.5-1.1, even more preferably 0.6-1.0.

[0071] Therefore, the mixed oxide prepared by the method of the present invention preferably has the characteristics of smaller particle size and narrower particle size distribution, which is helpful to achieve high-quality metal oxide doping and / or coating of active electrode materials for lithium ion batteries.

[0072] d value 10 d 50 and d 90 It is often used to characterize the cumulative particle size distribution of a given sample. For example, d 10 The diameter is smaller than d 10 The diameter of the particles when they occupy 10% of the sample volume, d 50 is less than d 50 The diameter of the particles when they occupy 50% of the sample volume.50 Also called the “volume median diameter” because it divides the sample equally by volume; d 90 is less than d 90 The diameter of the particles at which 90% of the sample volume is occupied.

[0073] The mixed oxide prepared by the process according to the invention preferably has a tapped density of 20 g / L to 1000 g / L.

[0074] The unheat-treated mixed oxide prepared by the process according to the invention preferably has a tapped density of 20 g / L-200 g / L, more preferably 30 g / L-150 g / L, even more preferably 40 g / L-130 g / L, still more preferably 50 g / L-120 g / L.

[0075] The heat-treated mixed oxide prepared by the process according to the invention preferably has a tapped density of 400 g / L to 1000 g / L, more preferably 450 g / L to 800 g / L, even more preferably 500 g / L to 700 g / L.

[0076] The tamped density of powdery or coarse-grained granular materials can be determined in accordance with DIN ISO 787-11:1995 "General methods of test for pigments and extenders--Part 11: Determination of tamped volume and apparent density after tamping". This involves measuring the apparent density of the bed after stirring and tamping.

[0077] The mixed oxide prepared by the inventive method is preferably hydrophilic in nature, i.e. it is not further processed by any hydrophobic reagent such as silane after being synthesized by flame spray pyrolysis process. The particles produced in this way usually have a purity of at least 96 % by weight, preferably at least 98 % by weight, more preferably at least 99 % by weight, wherein 100% purity refers to that the mixed oxide only comprises specified metal and oxygen. The mixed oxide can comprise a hafnium compound in the form of hafnium dioxide. Based on ZrO , the ratio of hafnium dioxide can be 1 to 4 % by weight. Based on the quality of the mixed oxide powder, the content of chloride is preferably less than 0.5 % by weight, more preferably less than 0.1 % by weight. Based on the quality of the mixed oxide powder, the ratio of carbon is preferably less than 2.0 % by weight, more preferably 0.005-1.0 % by weight, even more preferably 0.01-0.5 % by weight.

[0078] The mixed oxide is preferably a compound having the general formula

[0079] Li a Zr b M c O 0.5a+2b+d (I),

[0080] in

[0081] 1.5≤a≤15, preferably 1.8≤a≤12;

[0082] 0.5≤b≤3.0, preferably 0.8≤b≤3.0;

[0083] 0≤c≤5, preferably 1.5≤c≤4

[0084] For M = Na, K, d = 0.5c;

[0085] For M=Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, d=c;

[0086] For M = B, Al, Ga, In, Fe, Sc, Y, La, d = 1.5c;

[0087] For M = Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, d = 2c,;

[0088] For M = V, Nb, Ta, d = 2.5c;

[0089] For M=Mo, W, d=3c.

[0090] In the general formula (I), M can be one or more elements selected from Na, K, Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, B, Al, Ga, In, Fe, Sc, Y, La, Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, V, Nb, Ta, Mo, and W. Preferably, M=La and Al.

[0091] The present invention also provides a mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal,

[0092] in

[0093] - the mixed oxide is in the form of aggregated primary particles,

[0094] -With 15-50m 2 / g BET surface area,

[0095] - Number average particle size d of 0.1-2 μm as determined by static light scattering (SLS) 50 ,and

[0096] - 50-200g / L compacted density.

[0097] Such mixed oxides can be prepared by the process according to the invention without further thermal treatment.

[0098] The present invention also provides a mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal,

[0099] in

[0100] - the mixed oxide is in the form of aggregated primary particles,

[0101] -With a length less than 10m 2 / g, preferably 0.1-10m 2 / g BET surface area,

[0102] - Number average particle size d of 1-50 μm as determined by static light scattering (SLS) 50 ,and

[0103] -400-1000g / L compacted density.

[0104] Such mixed oxides can be prepared by the process according to the invention, with a further thermal treatment and optionally a ball milling process.

[0105] The invention also provides mixed oxides obtainable by the process according to the invention.

[0106] Use of mixed oxides in lithium-ion batteries

[0107] The present invention also provides the use of the mixed oxide according to the invention or the mixed oxide obtainable by the process according to the invention in lithium ion batteries, in particular as a component of a solid electrolyte for lithium ion batteries, as an additive in liquid electrolytes or gel electrolytes or as a component of electrodes for lithium ion batteries.

[0108] The invention also provides a lithium-ion battery comprising the mixed oxide according to the invention or a mixed oxide obtainable by the process according to the invention.

[0109] In addition to an active positive electrode (cathode), the lithium-ion battery of the invention may also comprise an anode, a separator and an electrolyte comprising a lithium-containing compound.

[0110] The positive electrode (cathode) of a lithium-ion battery generally includes a current collector and an active cathode material layer formed on the current collector.

[0111] The current collector may be an aluminum foil, a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.

[0112] The active positive electrode material may include materials that can reversibly insert / deinsert lithium ions and are well known in the art. Such active positive electrode materials may include transition metal oxides, such as mixed oxides containing Ni, Co, Mn, V or other transition metals and optionally lithium. The mixed lithium transition metal oxide preferably used as the active positive electrode material is selected from lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide, lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide or mixtures thereof. The mixed lithium transition metal oxide preferably has the general formula LiMO2, wherein M is at least one transition metal selected from nickel, cobalt, manganese; more preferably M=Co or Ni x Mn y Co z , where 0.3≤x≤0.9, 0≤y≤0.45, 0≤z≤0.4.

[0113] The anode of the lithium ion battery may include any suitable material that is commonly used in secondary lithium ion batteries and can reversibly intercalate / deintercalate lithium ions. Typical examples thereof are carbonaceous materials, including crystalline carbon, such as natural or artificial graphite in the form of plate-like, flaky, spherical or fibrous graphite; amorphous carbon, such as soft carbon, hard carbon, mesophase pitch carbide, burnt coke or a mixture thereof. In addition, lithium metal or conversion materials (such as Si or Sn) can be used as anode active materials.

[0114] The electrolyte of a lithium-ion battery can be in liquid, gel or solid form.

[0115] The liquid electrolyte of the lithium-ion battery may include any suitable organic solvent commonly used in lithium-ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinylethylene carbonate, or mixtures thereof.

[0116] The gel electrolyte includes a gel polymer.

[0117] Solid electrolytes for lithium-ion batteries may comprise oxides, such as lithium metal oxides, sulfides, phosphates, or solid polymers.

[0118] The liquid or polymer gel electrolyte of lithium-ion batteries generally contains lithium salts. Examples of such lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis-2(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trifluoromethanesulfonate, LiN(SO2CF2CF3)2, lithium nitrate, lithium bis(oxalate)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide lithium, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide lithium, and mixtures thereof.

[0119] Lithium ion batteries, especially those with liquid or gel electrolytes, may also include a separator to prevent direct contact between the two electrodes, which would result in an internal short circuit.

[0120] The material of the diaphragm may include polyolefin resins, fluorinated polyolefin resins, polyester resins, polyacrylonitrile resins, cellulose resins, nonwoven fabrics or mixtures thereof. Preferably, the material includes polyolefin resins such as polyethylene or polypropylene based polymers, fluorinated resins such as polyvinylidene fluoride polymers or polytetrafluoroethylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyacrylonitrile resins, cellulose resins, nonwoven fabrics or mixtures thereof.

[0121] BRIEF DESCRIPTION OF THE DRAWINGS

[0122] Figure 1A and 1B is a TEM image of Li—La—Zr—Al mixed oxide particles prepared as described in Comparative Example 1.

[0123] Figure 2A and 2B is a TEM image of Li—La—Zr—Al mixed oxide (LLZO) particles prepared as described in Comparative Example 2.

[0124] Figure 3A and 3B is a TEM image of Li—La—Zr—Al mixed oxide (LLZO) particles of the present invention prepared as described in Example 1.

[0125] Figure 4 The XRD patterns of the Li-La-Zr-Al mixed oxide (LLZO) of the present invention prepared as described in Examples 1-3 are shown.

[0126] Figure 5 SEM-EDX mapping images of La (white) on LLZO-coated NMC prepared using LLZO prepared as described in Example 1 are shown.

[0127] Figure 6 SEM-EDX mapping images of La (white) on LLZO-coated NMC prepared using LLZO prepared as described in Comparative Example 1 are shown.

[0128] Figure 7 Statistical analysis of the area distribution of La in the SEM-EDX imaging images of LLZO-coated NMC prepared using LLZO prepared as described in Comparative Example 1 and Example 1 is shown.

[0129] Figure 8 Initial impedance test results of all-solid-state lithium metal batteries with LLZO prepared as described in Examples 2 and 3 and without LLZO (PEO) measured by electrochemical impedance spectroscopy (EIS) are shown.

[0130] Fig. 9 Initial formation results for all-solid-state lithium metal batteries with LLZO prepared as described in Examples 2 and 3 and without LLZO (PEO) at 60°C and 0.1C between 3.0V and 4.3V are shown. DETAILED DESCRIPTION

[0131] Example

[0132] BET surface area 0.30-0.60 m 2 / g, median particle size d 50 =10.6±2 μm (determined by static laser scattering method) was provided by Linyi Gelon LIB Co.

[0133] The average molecular weight is 4 x 10 5 g / mol of commercially available polyethylene oxide (PEO from Sigma-Aldrich) was used for electrolyte formulation. PEO was used as received. Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) from Kishida with a purity of >99% (battery grade) was used as received in a glove box.

[0134] Commercially available copper foil with lithium deposited thereon was purchased from Honjo Metal, and the thickness of the copper layer was 10 μm, and the thickness of the lithium layer was 20 μm.

[0135] Comparative Example 1

[0136] (Li-La-Zr-Al mixed oxide from aqueous nitrate precursor solution)

[0137] 18.63 kg of an aqueous solution containing 1142 g of LiNO3, 2839 g of La(NO3)3*6H2O, 1670 g of Zr(NO3)4 (metal content: 24 wt%) and 212 g of Al(NO3)3*9H2O was prepared under constant stirring until a clear solution was obtained. This solution corresponds to the composition Li 7.54 La3Zr2Al 0.26 O 12.66 .

[0138] 2.5 kg / h of this solution and 15 Nm 3 / h of air is formed into an aerosol through a two-component nozzle and sprayed into a tubular reactor under the condition of a burning flame. The combustion gas of the flame is 20Nm 3 / h of hydrogen and 75Nm 3 / h of air composition, resulting in a controlled temperature of 900 °C at the measuring point 1 m below the nozzle. In addition, a 25 Nm 3 / h of secondary air. After the reactor, the reaction gas is cooled and filtered.

[0139] The particle properties are shown in Table 1 and the TEM images of the particles are shown in Figure 1A and 1B as shown in .

[0140] Preparation of NMC powder coated with Li-La-Zr-Al mixed oxide of Comparative Example 1:

[0141] NMC powder (99 g) was first mixed with 1.0 g (1 wt%) of the fumed powder of Comparative Example 1 in a high intensity laboratory mixer (Somakon mixer MP-GL with 0.5 L mixing unit) at 500 rpm (specific electrical power: 350 W / kg NMC) for 1 minute to uniformly mix the two powders. The mixing intensity was then increased to 2000 rpm (specific electrical power: 800 W / kg NMC, tip speed of the mixing tool in the mixing unit: 10 m / s) and mixing was continued for 5 minutes to achieve dry coating of the NMC particles with the fumed powder of Comparative Example 1.

[0142] Comparative Example 2

[0143] (Li-La-Zr-Al mixed oxide from nitrate precursor ethanol solution)

[0144] 18.3 kg of an ethanol solution containing 779 g of LiNO3, 1930 g of La(NO3)3*6H2O, 1139 g of Zr(NO3)4 (metal content: 24 wt%) and 146 g of Al(NO3)3*9H2O was prepared under constant stirring until a clear solution was obtained. This solution corresponds to the composition Li 7.54 La3Zr2Al 0.26 O 12.66 .

[0145] 2.5 kg / h of this solution and 15 Nm 3 / h of air is formed into an aerosol through a two-component nozzle and sprayed into a tubular reactor under the condition of a burning flame. The combustion gas of the flame is 13.7Nm 3 / h of hydrogen and 75Nm 3 / h of air composition, resulting in a controlled temperature of 900 °C at the measuring point 1 m below the nozzle. In addition, a 25 Nm 3 / h of secondary air. After the reactor, the reaction gases are cooled and filtered.

[0146] The particle properties are shown in Table 1 and the TEM images of the particles are shown in Figure 2A and 2B as shown in .

[0147] Example 1

[0148] (Li-La-Zr-Al mixed oxide)

[0149] 1320 g of a commercial solution (Octa Zirconium 12) was mixed with 173 g of acetylacetone. The solution was stirred continuously and mixed with 2273 g of a commercial solution containing 2 wt% of Li in the form of lithium neodecanoate ( Deca Lithium 2) was mixed. Another solution containing 1125 g La(NO3)3*6H2O, 83.3 g Al(NO3)3*9H2O, 2660 g ethanol and 2660 g ethylhexanoic acid (ethanol:ethylhexanoic acid molar ratio = 3.1:1, water content in the solvent mixture is 2.7 wt%) was added under constant stirring until a clear solution was obtained. This solution corresponds to the composition Li 7.54 La3Zr2Al 0.26 O 12.66 .

[0150] 2.5 kg / h of this solution and 15 Nm 3 / h of air is formed into an aerosol through a two-component nozzle and sprayed into a tubular reactor under the condition of a burning flame. The combustion gas of the flame is 12.9Nm 3 / h of hydrogen and 75Nm 3 / h of air composition, resulting in a controlled temperature of 900 °C at the measuring point 1 m below the nozzle. In addition, a 25 Nm 3 / h of secondary air. After the reactor, the reaction gases are cooled and filtered.

[0151] The particle properties are shown in Table 1 and the TEM images of the particles are shown in Figure 3A and 3B as shown in .

[0152] Preparation of NMC powder coated with Li-La-Zr-Al mixed oxide of Example 1:

[0153] NMC powder (99 g) was first mixed with 1.0 g (1 wt%) of the fumed powder of Example 1 in a high intensity laboratory mixer (Somakon mixer MP-GL with 0.5 L mixing unit) at 500 rpm (specific electrical power: 350 W / kg NMC) for 1 minute to uniformly mix the two powders. The mixing intensity was then increased to 2000 rpm (specific electrical power: 800 W / kg NMC, tip speed of the mixing tool in the mixing unit: 10 m / s) and mixing was continued for 5 minutes to achieve dry coating of the NMC particles with the fumed powder of Example 1.

[0154] Example 2

[0155] (Calcined Li-La-Zr-Al mixed oxide)

[0156] The mixed oxide obtained in Example 1 was calcined in a rotary kiln at 950°C for 6 hours. XRD analysis ( Figure 4 ) showed that the main phase of the product was cubic garnet structure.

[0157] Example 3

[0158] (Calcined and ball-milled Li-La-Zr-Al mixed oxide)

[0159] The mixed oxide obtained in Example 2 was further ball-milled in ethanol using ZrO2 balls with a diameter of 0.5 mm. XRD analysis ( Figure 4 ) showed that the main phase of the product was still cubic garnet structure.

[0160] Table 1: Properties of mixed oxides

[0161] Example <![CDATA[BET[m 2 / g]]]> <![CDATA[D 10 [μm]]]> <![CDATA[D 50 [μm]]]> <![CDATA[D 90 [μm]]]> Compacted density [g / L] Comparative Example 1 19 0.20 1.55 5.34 195 Comparative Example 2 21 0.19 1.46 4.67 226 Example 1 25 0.09 0.97 4.70 98 Example 2 <1 8.31 19.13 42.36 788 Example 3 10 0.41 0.93 5.78 680

[0162] Analysis of mixed lithium transition metal oxides coated with LLZO by SEM-EDX

[0163] Figure 5 The SEM-EDX imaging image of La (white) on NMC coated with LLZO prepared by gas phase nano-LLZO (Example 1) is shown. Figure 6 The analysis results of NMC coated with crude LLZO from the gas phase process (Comparative Example 1) are shown. Figure 5 and 6 The axes represent: x-axis = particle diameter; left y-axis = volume percentage, right y-axis = cumulative volume percentage. The NMC mixed oxide dry-coated with gas phase nano-LLZO (Example 1) shows that all NMC particles are completely and evenly covered by LLZO ( Figure 5No large LLZO agglomerates were detected, indicating good dispersibility of the nanostructured gas phase nano-LLZO. In addition, no free unattached LLZO particles were found near the NMC particles, indicating strong adhesion between the coating and the substrate (NMC). In contrast, Figure 6 It shows that only the fine LLZO particles of the fumed coarse LLZO are attached to the surface of the NMC particles. The larger LLZO particles are non-dispersed and therefore located near the NMC particles without being attached. As a result, the NMC particles are not completely covered by zirconia.

[0164] Figure 7 Statistical analysis of Example 1 and Comparative Example 1 is shown. The La (white) (unit: μm) in the SEM-EDX image was further analyzed by a box normal plot. 2 ), which shows a clear difference in the dispersion of La (white) between Example 1 and Comparative Example 1.

[0165] Preparation of hybrid solid electrolyte (HSE) membrane

[0166] LLZO ceramic powder was mixed with polyethylene oxide (PEO) and LiTFSI and subjected to a solvent-free hot pressing process to produce flexible and self-supporting membranes. Two sets of composite membranes with LLZO from Example 2 and Example 3 have been prepared according to Table 2. The weighed HSE membrane of LLZO was ground, ground with PEO and weighed LLZO to obtain a paste material, which was then annealed at 100°C overnight and continuously hot pressed between Teflon substrates at 100°C to the desired thickness of about 110 μm.

[0167] Table 2: Formulation of hybrid solid electrolyte

[0168] EO / Li PEO+LiTFSI(g) LLZO(g) LLZO wt% LLZO Type 15 0.697+0.303 0.42 30% Example 2 15 0.697+0.303 0.42 30% Example 3

[0169] Assembly and characterization of all-solid-state lithium metal batteries

[0170] Three groups of all-solid-state NMC_HSE_Li metal batteries were assembled using (a) PEO without LLZO filler, (b) PEO with calcined LLZO (Example 2) filler, and (c) PEO with ball-milled LLZO (Example 3) filler. The initial impedance was analyzed by electrochemical impedance spectroscopy (EIS), and the results are shown in Figure 8 . Fig. 9 The initial formation of the three cells at 60°C and 0.1 C between 3.0 V and 4.3 V is shown. The cell using LLZO from Example 3 has the highest capacity at 140 mAh / g at 0.1 C discharge and the lowest impedance of the three examples.

Claims

1. A process for producing a mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal by flame spray pyrolysis, Features The method uses At least one metal precursor solution comprising - lithium carboxylates and / or zirconium carboxylates, wherein each of these metal carboxylates contains from 5 to 20 carbon atoms, and - a solvent mixture comprising an alcohol containing 5 to 20 carbon atoms and a carboxylic acid, wherein the solvent mixture comprises less than 10% by weight of water and wherein the molar ratio of alcohol to carboxylic acid is between 1:20 and 20:

1.

2. The method according to claim 1, characterized in that The flame spray pyrolysis comprises the following steps: a) atomizing at least one metal precursor solution by means of an atomizer gas to provide an aerosol, b) reacting the aerosol in the reaction space of the reactor with a flame obtained by igniting a mixture of fuel gas and oxygen-containing gas to obtain a reaction stream, c) cooling the reaction stream and d) subsequently removing the solid metal oxide from the reaction stream.

3. The method according to claim 1 or 2, characterized in that The mixed oxide has the general formula Li a Zr b M c O 0.5a+2b+d Compound (I) in 1.5≤a≤15, 0.5≤b≤3.0, 0≤c≤5, For M = Na, K, d = 0.5c; For M=Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, d=c; For M = B, Al, Ga, In, Fe, Sc, Y, La, d = 1.5c; For M = Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, d = 2c; For M = V, Nb, Ta, d = 2.5c; For M=Mo, W, d=3c.

4. The method according to claim 1 or 2, characterized in that The mixed oxide has 0.1-100 m 2 / g of BET surface area.

5. The method according to claim 1 or 2, characterized in that The lithium carboxylate and the zirconium carboxylate are independently carboxylates selected from the following group: linear, branched or cyclic pentanoates, hexanoates, heptanoates, octanoates, nonanoates, decanoates, undecanoates, dodecanoates, tridecanoates, tetradecanoates, pentadecanoates, hexadecanoates, heptadecanates, octadecanoates, nonadecanates and mixtures thereof of lithium and / or zirconium.

6. The method according to claim 1 or 2, characterized in that The alcohol is selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, n-pentanol, n-hexanol, cyclohexanol, n-octanol, 2-ethylhexanol, n-decanol, neodecanol and mixtures thereof.

7. The method according to claim 1 or 2, characterized in that The metal precursor solution comprises a chelating agent selected from diamines and 1,3-dicarbonyl compounds.

8. The method according to claim 1 or 2, characterized in that The mixed oxide has a number average particle size d as determined by static light scattering. 50 0.05-2μm.

9. The method according to claim 1 or 2, characterized in that The compacted density of the mixed oxide is 20-1000 g / L.

10. The method according to claim 1 or 2, further comprising heat treating the mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal produced by flame spray pyrolysis.

11. The method according to claim 10, wherein the heat treatment is performed at a temperature of 600°C to 1300°C.

12. The method according to claim 10, further comprising grinding a mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal produced by flame spray pyrolysis.

13. The method of claim 12, wherein the milling is ball milling.

14. A mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal obtainable by the process according to any one of claims 1 to 2 and 4 to 9, characterized in that The mixed oxide has the general formula Li a Zr b M c O 0.5a+2b+d Compound (I) in 1.5≤a≤15, 0.5≤b≤3.0, 0≤c≤5, For M = Na, K, d = 0.5c; For M=Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, d=c; For M = B, Al, Ga, In, Fe, Sc, Y, La, d = 1.5c; For M = Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, d = 2c; For M = V, Nb, Ta, d = 2.5c; For M = Mo, W, d = 3c; The mixed oxide is in the form of aggregated primary particles, With 15-50m 2 / g BET surface area, The number average particle size d is 0.1-2 μm as determined by static light scattering. 50 ,and 30-150g / L compacted density.

15. A mixed oxide comprising lithium, zirconium and optionally at least one non-Li non-Zr metal obtainable by the process according to any one of claims 10 to 11, characterized in that The mixed oxide has the general formula Li a Zr b M c O 0.5a+2b+d Compound (I) in 1.5≤a≤15, 0.5≤b≤3.0, 0≤c≤5, For M = Na, K, d = 0.5c; For M=Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, d=c; For M = B, Al, Ga, In, Fe, Sc, Y, La, d = 1.5c; For M = Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, d = 2c; For M = V, Nb, Ta, d = 2.5c; For M = Mo, W, d = 3c; The mixed oxide is in the form of aggregated primary particles, With less than 10m 2 / g BET surface area, The number average particle size d is 1-50 μm as determined by static light scattering. 50 ,and 400-1000g / L compacted density.

16. Use of the mixed oxide according to claim 14 or 15 as a component of a solid electrolyte for lithium-ion batteries, as an additive in liquid electrolytes or gel electrolytes or as a component of electrodes.

17. A lithium-ion battery comprising the mixed oxide according to claim 14 or 15.

Citation Information

Patent Citations

  • Aluminium-doped Li7La3Zr2O12 solid electrolyte and process for producing the same

    EP2159867A1

  • All-solid-state lithium battery

    JP4982866B2

  • Lithium positive electrode material and lithium battery

    US20170179544A1

  • Method for producing mixed oxide powder comprising lithium, lanthanum and zirconium

    WO2015173114A1

  • Process for preparing mixed metal oxide powders

    CN101466641A